Figs Are More Than Fallback Foods: The Relationship between Ficus and Cebus in a Tropical Dry Forest - Parr, Nigel A.; Melin, Amanda D.; Fedigan, Linda Marie (International Journal of Zoology, 2011)
In many studies on primate feeding ecology, figs (Ficus spp.) are characterized as fallback foods, utilized only when preferred sources of food are unavailable. However, for white-faced capuchin monkeys (Cebus capucinus) living in northwestern Costa Rica, figs are a consistently important resource and may increase groupwide energy intake. We investigated whether visits to figs affect ranging and behavioural patterns of capuchins. Although daily range length and average travel speed do not differ on days when fig trees are visited, capuchins spend more time in directed travel and more time stationary on “fig days”. Capuchins also increase time spent foraging for fruit and decrease time spent foraging for invertebrates on days when figs trees are visited. Capuchins experience higher energy intake and lower energy output on “fig” days. Thus, the patterns of foraging for figs support an energy-maximization strategy and constitute an important nutritional resource for capuchins.